Greenwashing and green brand equity: The moderating role of brand credibility - Herawati, Baiq Candra (Journal of Management and Business Insight, 2024)
Purpose-Changes in consumer interest patterns from conventional products to environmentally friendly products concern companies. Environmental issues are a concern for consumers and companies as evidence of increasing awareness of the environmental impact of a product. With the presence of environmentally friendly products, it is hoped that it can be one of the factors that preserve the environment while winning market competition. Based on this, this study seeks to analyze the effect of greenwashing on green brand equity while moderating brand credibility. Design/Methodology/Approach-This study analyzes the green brand equity of motorized vehicles in Indonesia. Sampling in this study used a purposive sampling technique, where respondents in certain areas were selected based on specific criteria, and 150 respondents were obtained. The data collection method uses a questionnaire distributed online. Then, the analytical tool used is Smart PLS with a bootstrapping process. Findings-The results prove that greenwashing has no positive effect on green brand equity, while brand credibility is proven to have a positive impact on green brand equity. Brand credibility has been proven to moderate (weaken) the relationship between greenwashing and green brand equity. Research limitations/implications-The limitation of this research is that the number of respondents still needs to be increased. In addition, respondents do not represent every motorcycle user in other regions of Indonesia. Therefore, the results of this study cannot yet describe the picture of motorized vehicle users in Indonesia when making purchasing decisions. The object of research is also still classified as specific, namely consumers of motorized vehicles, not using motor vehicles in general. Originality/value-This research is still very minimal conducted by previous researchers who used the object of motorized vehicle users in Indonesia. Generally, previous studies used different objects in certain regions.